Forecasting Fuel Consumption Kapal X Menggunakan Metode Sarima Di Penajam Supply Base (PSB) Pertamina Hulu Kalimantan Timur - Ardana, Wahyu; Andrianti, Irma (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The energy industry faces major challenges in fuel inventory management due to price and demand fluctuations. PT Pertamina Hulu Kalimantan Timur (PHKT) faces this issue in the operation of Ship X, the crucial transportation between Balikpapan and Penajam Supply Base (PSB). Uncertainty in fuel demand can disrupt worker mobility and increase operational costs due to the high frequency of deliveries. Therefore, forecasting fuel consumption is important for efficiency and smooth operation. The purpose of this research is to forecast the amount of fuel that will be used by Ship X. The method used is a quantitative approach by utilizing secondary data on fuel consumption for the period January to September 2024 from PSB PHKT. In forecasting efforts, the Seasonal Autoregressive Integrated Moving Average (SARIMA) (1,1,0)(0,1,1)6 model is used. The selection of this model is based on parameter significance and fulfillment of the white noise residual assumption after going through diagnostic tests. The results of the study provide a prediction of the fuel usage of Ship X in week 40 of 1794.37 liters.